PENGARUH BEBAN KERJA, DISIPLIN KERJA DAN KOMITMEN ORGANISASI (STUDI KASUS PADA PT UNITED TRACTORS PANDU ENGINEERING) - Rahmia Nurul Asdianti (2022)
This research is a quantitative study that aims to determine the effect of workload, work discipline and organizational commitment on employee performance. The sample in this study were employees at PT United Tractors Pandu Engineering. The sample used was 45 employees with the sampling method used, namely the saturated sample method. In this research hypothesis, namely to determine the partial and simultaneous effect of three independent variables on 1 dependent variable. Tests carried out included validity tests, reliability tests and hypothesis testing. From the tests that have been carried out, the results are: (1) Workload has a positive and significant effect on employee performance (2) Work discipline has a positive and significant effect on employee performance (3) Organizational commitment has a positive and significant effect on employee performance and (4) Burden work, work discipline and organizational commitment simultaneously affect employee performance.